2015
DOI: 10.1098/rsif.2015.0249
|View full text |Cite|
|
Sign up to set email alerts
|

Punctuated equilibrium in the large-scale evolution of programming languages

Abstract: The analogies and differences between biological and cultural evolution have been explored by evolutionary biologists, historians, engineers and linguists alike. Two well-known domains of cultural change are language and technology. Both share some traits relating the evolution of species, but technological change is very difficult to study. A major challenge in our way towards a scientific theory of technological evolution is how to properly define evolutionary trees or clades and how to weight the role playe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 57 publications
1
51
0
Order By: Relevance
“…Like biodiversity, model diversity can be organized in taxonomic structures to classify models. Using Wikipedia as a reference, such a taxonomic study has been done already for programming languages and showed a phylogenetic tree with new programming languages emerging from different elements of earlier programming languages (Valverde and Solé 2015). A similar study for AEMs is intriguing, but is beyond this study.…”
Section: Discussionmentioning
confidence: 99%
“…Like biodiversity, model diversity can be organized in taxonomic structures to classify models. Using Wikipedia as a reference, such a taxonomic study has been done already for programming languages and showed a phylogenetic tree with new programming languages emerging from different elements of earlier programming languages (Valverde and Solé 2015). A similar study for AEMs is intriguing, but is beyond this study.…”
Section: Discussionmentioning
confidence: 99%
“…The detection and patterning of these ruptures and continuities invites methodological experimentation, e.g. the use of phylogenetic methods (Mesoudi, 2011;Valverde and Solé, 2015), Big Data analytics (Manning, 2013) or scientometric techniques (Rotolo et al, 2015). In particular, a quantitative mapping of patterns in the evolution of rules and meta-rules is a promising research avenue as both MLP and TEP literatures have so far identified regimes and techno-economic paradigms on the basis of qualitative interpretation of historical data, resulting in a certain lack of analytical rigour.…”
Section: Deep Transitions and The Future: Bottom-up Vs Top-down Tranmentioning
confidence: 99%
“…There are many examples of hand-made diagrams of the evolution of programming languages but it is unclear how to obtain evolutionary trees in the absence of a 'cultural genome'. Recently, we have proposed a method to reconstruct these cultural phylogenies using networks of historical influences [62]. This network is an instance of directed graph G ¼ (V, E) formed by the set of programming languages V and a set E of influence links among them.…”
Section: Evolution Of Programming Languagesmentioning
confidence: 99%